تحليل الأخطاء في مهارة الكتابة لدى التلاميذ في مدرسة مفتاح العلوم المتوسطة الإسلامية كوندانج موجوكرطا - Siti Musyafa’atu Zahro; Syarifuddin Syarifuddin (Universitas Yudharta Pasuruan, 2019)
Arabic is the important language for Islamic people anyone. In Arabic school prepared to research reach the language basic competence, especially in four skills this research used writing skill, writing is a skill of language to indirectly communication, not through face to face each others. One of the things that can be done is analysis the errors and find solutions to overcome these problems. The purpose of this analysis was to determine the problematic errors writing skill in student assignments. To achieve these objectives, the researcher use descriptive research method with qualitative approaches. This study classifies each nahwu writing errors, sharaf, and letters, corrects and justify. For the data collection methods used are observation, interview, and documentation. Sources Of data taken from the student's task is to make a free bouquet using Arabic.From the results of samples taken 20 student researchers were able to nahwu because graduates on Islamic elementary school and also from schools that have previously been studied qoidah nahwu sharaf. whereas 10 students have not been able to understand of sharaf because not graduates on Islamic elementary school or from boarding school.